2021
DOI: 10.1016/j.esmoop.2021.100225
|View full text |Cite
|
Sign up to set email alerts
|

Care of the adult cancer patient at the end of life: ESMO Clinical Practice Guidelines

Abstract: Highlights This ESMO Clinical Practice Guideline provides key recommendations for end-of-life care for patients with advanced cancer. It details care that is focused on comfort, quality of life and approaching death of patients with advanced cancer. All recommendations were compiled by a multidisciplinary group of experts. Recommendations are based on available scientific data and the authors’ collective expert opinion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 102 publications
(221 reference statements)
4
57
0
3
Order By: Relevance
“…A few randomised controlled trials and systematic reviews addressing different types of tumours have shown some effect of different anticancer therapies on reducing pain and improving patients’ QoL 37–42. However, this issue is largely debated as evidence is controversial or lacking, so that the guideline from the European Society for Medical Oncology (ESMO) explicitly contraindicates the use of anticancer drugs in the last weeks of life 43…”
Section: Discussionmentioning
confidence: 99%
“…A few randomised controlled trials and systematic reviews addressing different types of tumours have shown some effect of different anticancer therapies on reducing pain and improving patients’ QoL 37–42. However, this issue is largely debated as evidence is controversial or lacking, so that the guideline from the European Society for Medical Oncology (ESMO) explicitly contraindicates the use of anticancer drugs in the last weeks of life 43…”
Section: Discussionmentioning
confidence: 99%
“…The importance of nursing staff in terminal care and survival prediction has been highlighted and emphasized by Crawford et al in the study of cancer patients. 5 This also had been endorsed earlier in two systematic reviews. 6 , 7 …”
mentioning
confidence: 59%
“…Clinicians are encouraged to discuss these possible scenarios with patients and their families before commencing interventions, such as total parenteral nutrition. As patients approach the end of their lives, their goals of care may shift from disease management and life prolongation to symptom management and quality of life [11].…”
Section: Advanced Care Planning and Goals Of Care Conversationsmentioning
confidence: 99%